2020
DOI: 10.3390/catal11010015
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Oxidation of CO over CoFe2O4 and M/CoFe2O4 (M = Ce, Co, Cu or Zr) Catalysts

Abstract: CoFe2O4 prepared by sol-gel has been examined with respect to its catalytic performance for preferential CO oxidation in a H2-rich stream. In turn, the promoting effects of incorporation of Ce, Co, Cu, and Zr by impregnation on the surface of CoFe2O4 on the process are examined as well. The catalysts have been characterized by N2 adsorption, X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), temperature programmed reduction (TPR), and X-ray photoelectron spectra (XPS), as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The peaks with high B.E. >530 eV can be due to surface oxygen species of lattice defects [31,32]. According to ZHAO Kun et.al [33], those peaks are attributed to the adsorbed oxygen (O 2 2− , O 2 1− ) which is interrelated to the oxygen vacancies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The peaks with high B.E. >530 eV can be due to surface oxygen species of lattice defects [31,32]. According to ZHAO Kun et.al [33], those peaks are attributed to the adsorbed oxygen (O 2 2− , O 2 1− ) which is interrelated to the oxygen vacancies.…”
Section: Resultsmentioning
confidence: 97%
“…The high-resolution Co 2p spectrum, depicted in Fig. 5:c, consists of two spin-orbit doublets Co 2p3/2 characterized for Co 2+ , and Co 3+ in B-sites [31,32]. While the detected Co 2p1/2 peak is categorized for Co 2+ in B sites.…”
Section: Resultsmentioning
confidence: 99%
“…The low binding energy < 530 eV was owing to the Fe/ Ca-O and Fe/Sr-O bonds [53]. Higher binding energy peaks > 530 eV can be attributed to the surface oxygen species of lattice defects [53,54]. According to ZHAO Kun et al [55], the observed peaks can be due to the adsorbed oxygen (O 2 2− , O 2 1− ), which is interrelated to the oxygen vacancies.…”
Section: Xps Analysesmentioning
confidence: 97%
“…11−16 More specifically, the performance of iron-zirconia solid solutions has been investigated in these systems 17−21 although the use of CoFe 2 O 4 mixed oxide resulted in high CO conversions (about 80%) and good stability (during 30 h) at 250 °C in the CO-PROX reaction. 22 The use of dual metal Fe−Co single sites on N-doped carbon supports has also been investigated by Wang, 17 concluded that CO adsorption occurs on the Co sites and that oxygen dissociation takes place on the Fe sites.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe and Cu were found to be incorporated into a Cu−Fe supersaturated solid solution, which improved the CO oxidation activity, with carbon dioxide and water produced selectively with high catalytic activity in depleted hydrogen streams. The preferential oxidation of CO over CoFe 2 O 4 promoted with M/CoFe 2 O 4 (M = Ce, Co, Cu, or Zr) was studied by Bejaoui et al 22 Indeed, the mixed oxides have structures and morphologies that are active in the PROX reaction and other oxidation processes. The vacancies within mixed oxide compounds favor the oxidation process, depending upon the specific metal oxides or materials utilized to increase oxygen storage within the lattice framework of the oxide.…”
Section: Introductionmentioning
confidence: 99%